Policy Review on Restaurant Taxes Levied on Warung Tegal in DKI Jakarta - Sukmana, Arifin (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2011)
The study analyzes the restaurant tax levied on Warung Tegal1 in DKI Jakarta and provides solutions for such. Descriptive-qualitative approach (Creswell, 2009) is used, employing both interview and library research. Results suggest that restaurants of every type, including Warung Tegal, have been taxed since 2003. The controversy was caused by negligence of excise officers in socializing the law and blow-ups by the media. The feared concomitant problems of the policy enactment are: revenue threshold exempted from the taxes is too low and the collection system is inefficient. The solutions proposed are raising the threshold and implementing the official assessment system to assess the amount of accrued taxes. Keywords: restaurant tax, warung tegal